Open and impactful academic publishing - Ciriminna, Rosaria; Li Petri, Giovanna; Angellotti, Giuseppe; Luque, Rafael; Pagliaro, Mario (Frontiers in Research Metrics and Analytics, 2025)
IntroductionThe advantages of self-archiving research articles on institutional repositories or personal academic websites are numerous and relevant for society and individual researchers. Yet, self-archiving has been adopted by a small minority of active scholars.MethodsAiming to further inform educational work on open and impactful academic publishing in the digital era, we posed selected questions to Stevan Harnad 30 years after his "subversive proposal" to maximize research impact by self-archiving scholarly articles in university-hosted or disciplinary online repositories to make published articles openly available.Results and discussionSelf-archiving is even more needed today than it was when Professor Harnad called for it when the World Wide Web was in its infancy; OA academic publishing is a necessary but not sufficient condition for impactful research; self-archiving on a personal academic website is often more effective than in institutional repositories.